Perkembangan Pasar Ternak Muaro Paneh Tahun 2001-2021 - Handayani, Fitri; Rusdi, Rusdi (Lembaga Yasin AlSys, 2025)
This study examines the development of the Muaro Paneh cattle market in Bukit Sundi District. The focus of this study is on the development of the Muaro Paneh cattle market and its impact on Nagari Muaro Paneh in 2001-2021. The importance of this research is because the development and existence of the Muaro Paneh cattle market has an impact on the people of Nagari Muaro Paneh and its surroundings, as well as being the wealth treasure of the nagari in improving the economy of Nagari Muaro Paneh. This study uses historical methods consisting of heuristics, verification or source criticism, interpretation, and historiography. Based on the results of this study, the development of the Muaro Paneh cattle market has an influence on the economy of the community around the market and the development of the market area. In the development of the livestock market, changes occur in the form of market buildings or in the physical development sector, as well as in the social, economic, and educational sectors. These changes are marked by changes in the existing buildings around the Muaro Paneh cattle market and the increasing economy of the people of Nagari Muaro Paneh.